Taxonomical considerations and molecular phylogeny of the closely related genera Bitylenchus, Sauertylenchus and Tylenchorhynchus (Nematoda: Telotylenchinae), with one new and four known species from Iran. (1st October 2020) - Hosseinvand, M.; Eskandari, A.; Ganjkhanloo, S.; Ghaderi, R.; Castillo, P.; Palomares-Rius, J.E.
Abstract: During several nematological surveys in cultivated and natural habitats in Khuzestan and Zanjan provinces of Iran, a new species, Bitylenchus parvulus n. sp., two new records for Iran – namely, Tylenchorhynchus agri and Tylenchorhynchus graciliformis – and a population of Bitylenchus parvus and one of Sauertylenchus maximus were recovered and characterized based upon morphological and molecular approaches. The new species is characterized by lip region with five to seven annuli, stylet 17.7 (17.0–18.5) μm long, sub-cylindrical tail narrowing abruptly near terminus giving a bluntly digitate shape to the tail tip, cuticle near anterior part of vulva wrinkled and post-rectal sac occupies whole of tail cavity. The phylogenetic analyses were carried out using molecular data from D2–D3 expansion segments of large ribosomal subunit (28S rRNA) for all studied species and the partial small ribosomal subunit (18S rRNA) for the new species. The representatives of Bitylenchus and Sauertylenchus formed distinct clades from Tylenchorhynchus members, supporting the hypothesis in which Bitylenchus and Sauertylenchus could be considered as valid genera, but rejecting the 'large-genus' concept for Tylenchorhynchus . Also, Sauertylenchus ibericus was proposed as a junior synonym of S. maximus based on the results from morphological and phylogenetic analysis. Furthermore, an identification key for all known species included in the three genera Bitylenchus, Tylenchorhynchus and Sauertylenchus is presented herein. The number of transverse annuli on the lip region and presence/absence of post-rectal sac were considered as the main diagnostic characters for classifying the species into seven groups, and other morphological and morphometric characters were subsequently used for distinguishing species in each group.